Positive Effects of Education on Cognitive Functioning Depend on Clinical Status and Neuropathological Severity - Jansen, Michelle G.; Geerligs, Linda; Claassen, Jurgen A. H. R.; Overdorp, Eduard J.; Brazil, Inti A.; Kessels, Roy P. C.; Oosterman, Joukje M. (Frontiers in Human Neuroscience, 2021)
Background: Variability in cognitive functions in healthy and pathological aging is often explained by educational attainment. However, it remains unclear to which extent different disease states alter protective effects of education. We aimed to investigate whether protective effects of education on cognition depend on 1) clinical diagnosis severity, and 2) the neuropathological burden within a diagnosis in a memory clinic setting. Methods: In this cross-sectional study, we included 108 patients with subjective cognitive decline (SCD, median age 71, IQR [66‐78], 43% men), 190 with mild cognitive impairment (MCI, median age 78, IQR [73‐82], 44% men), and 245 with Alzheimer’s disease dementia (AD) (median age 80, IQR [76‐84], 35% men). We combined visual ratings of hippocampal atrophy, global atrophy, and white matter hyperintensities on MRI into a single neuropathology score. To investigate whether the contribution of education to cognitive performance differed across SCD, MCI, and AD, we employed several multiple linear regression models, stratified by diagnosis and adjusted for age, sex, and neurodegeneration. We re-ran each model with an additional interaction term to investigate whether these effects were influenced by neuropathological burden for each diagnostic group separately. False discovery rate (FDR) corrections for multiple comparisons were applied. Results: We observed significant positive associations between education and performance for global cognition and executive functions (all adjusted p-values < 0.05). As diagnosis became more severe, however, the strength of these associations decreased (all adjusted p-values < 0.05). Education related to episodic memory only at lower levels of neuropathology in SCD (β = -0.23, uncorrected p = 0.02), whereas education related to episodic memory in those with higher levels of neuropathology in MCI (β = 0.15, uncorrected p = 0.04). However, these interaction effects did not survive FDR-corrections. Conclusions: Altogether, our results demonstrated that positive effects of education on cognitive functioning reduce with diagnosis severity, but the role of neuropathological burden within a particular diagnosis was small and warrant further investigation. Future studies may further unravel the extent to which different dimensions of an individual’s disease severity contribute to the waxing and waning of protective effects in cognitive aging.